Digitalization for Governance and Compliance: A Systematic Review of E-Invoicing and E-Filing Systems - Aynil Ajijar Hamdani; Sambas Ade Kesuma; Fahmi Natigor Nasution; Keulana Erwin (STMIK Indonesia Banda Aceh, 2026)
This study reviews global research on digital transformation, examining how e-invoicing, e-filing, digital port systems, and supply-chain data integration affect governance and compliance. the digitalization improves transparency, efficiency, and compliance, though regulatory differences remain a challenge. This research employs a literature review method by analyzing scholarly articles relevant to the topic. Digital transformation such as e-invoicing, e-filing, digital platforms, and supply-chain data integration improve governance, transparency, and efficiency. Real-time data and fewer manual errors enhance auditability. Evidence from several countries confirms better payment accuracy, logistics performance, and tax compliance, though regulatory harmonization especially within the EU remains a challenge. This study integrates cross-country evidence to clarify fragmented findings, showing that digitalization enhances transparency, reduces information asymmetry, and strengthens compliance across regulatory contexts. This study shows that digital tools improve transparency, efficiency, and compliance, guiding policymakers in adopting integrated platforms to reduce fraud and strengthen governance. This study is limited by its reliance on a literature review method, constrained to articles published within specific timeframes and academic databases.